1995
DOI: 10.1007/bf00858984
|View full text |Cite
|
Sign up to set email alerts
|

Management of congenital nephrotic syndrome of the Finnish type

Abstract: Congenital nephrotic syndrome of the Finnish type (CNF) is a rare autosomal recessively inherited disease characterised by intrauterine onset of massive urinary loss of proteins, 90% of which is albumin. The CNF gene has been localised to the long arm of chromosome 19, but the pathogenesis remains unclear. Historically, all CNF patients died, usually within the first 6 months of life. Today, a normal life can be achieved for a child with CNF by correcting the protein deficiency and normalising nutrition. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
150
0
21

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(171 citation statements)
references
References 37 publications
0
150
0
21
Order By: Relevance
“…15,19,20,23 Thus, the recent identification of the NPHS1 gene 14 responsible for this disease phenotype has suggested that this gene and the respective protein product nephrin play some key roles in the maintenance of the glomerular filtration barrier. Kestilä et al 14 showed that NPHS1 encodes a putative transmembrane protein with sequence similarity to that of cell adhesion molecules of the immunoglobulin superfamily and with expression in the kidney but not in other tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,19,20,23 Thus, the recent identification of the NPHS1 gene 14 responsible for this disease phenotype has suggested that this gene and the respective protein product nephrin play some key roles in the maintenance of the glomerular filtration barrier. Kestilä et al 14 showed that NPHS1 encodes a putative transmembrane protein with sequence similarity to that of cell adhesion molecules of the immunoglobulin superfamily and with expression in the kidney but not in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The current treatment of CNF with early nephrectomy and final renal transplantation appears to cure all symptoms. 15 After transplantation, no new symptoms are reported after several years of followup. The results of Kestilä et al 14 showed that NPHS1 is only expressed in the kidney glomerulus.…”
mentioning
confidence: 98%
“…30 Kidney transplantation within the first year can safe the life of nephrindeficient children. 31 These children are free from any symptoms in other nephrin-expressing tissues 32,33 except for an increase in muscular dystonia and mild ataxia in some cases. 34 In the present study, it is shown that induction of transgenic rat nephrin expression early during embryonic development (E11) exclusively in the podocytes rescues nephrin deficient mice from perinatal death.…”
Section: Discussionmentioning
confidence: 99%
“…Therapies with agents to reduce the glomerular filtration pressure have not been successful in reducing the proteinuria. Children with CNF are currently treated with bilateral nephrectomy and dialysis, followed by renal transplantation [58,59].…”
Section: Nephrin In Congenital Nephrotic Syndrome Of Finnish Typementioning
confidence: 99%